Non-heart-beating versus cadaveric and living-donor livers: differences in inflammatory markers before transplantation - Jassem, Wayel; Koo, Dicken D H; Muiesan, Paolo; Cerundolo, Lucia; Rela, Mohamed; Fuggle, Susan V; Heaton, Nigel D (Transplantation, 2003)
Liver transplantation from non-heart-beating donors (NHBD) has been reintroduced into clinical practice to increase the donor pool; however, little is known about the immune status of NHBD livers. The aim of this study was to assess intragraft cell populations and inflammatory markers in NHBD and to compare the findings with cadaveric and living-related donor (LRD) livers. Biopsy specimens were obtained from controlled NHBD (n=9), conventional cadaveric (n=22), and living-donor (n=10) livers at the end of cold storage. Cryostat sections were stained for monocytes-macrophages, T lymphocytes, and intercellular adhesion molecule (ICAM)-1. The levels of leukocyte infiltration in NHBD reflected those found in conventional cadaver donors and were significantly higher than in LRD livers. Similar levels of CD68+ monocytes-macrophages were detected in cadaver (4.0+/-1.2%) and NHBD livers (4.6+/-1.2%) and were significantly greater than in the LRD livers (2.6+/-0.5%, P<0.01). Furthermore, the levels of T lymphocytes in NHBD (1.1+/-0.6%) and cadaver donors (1.5+/-0.8%) were similar, and were higher than in LRD (vs. 0.47+/-0.3%, P<0.05). Twelve of 22 (60%) cadaver livers had high levels of ICAM-1 expression (grade 3), compared with only 1 of 10 (10%) LRD livers (P=0.02). Four of nine (44%) controlled NHBD livers expressed high levels of ICAM-1. The results demonstrate that livers obtained from controlled NHBD before transplantation are similar to conventional cadaver donors regarding the level of leukocyte infiltration. Nevertheless, lower levels of ICAM-1 were detected in NHBD, suggesting less exposure to inflammatory mediators than conventional cadaver donor livers.